Varicella Zoster Virus Vasculopathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The clinical, CSF, imaging, and virological features of varicella zoster virus (VZV) vasculopathies in 30 patients (7 children) are reviewed by researchers at various centers in the US and internationally.